Power-loss breakdown of a 750-V, 100-kW, 20-kHz bidirectional isolated DC-DC converter using SiC-MOSFET/SBD dual modules - Akagi H.; Yamagishi T.; Tan N.M.L.; Kinouchi S.-I.; Miyazaki Y.; Koyama M. (IEEE Computer Society, 2023)
This paper describes the design, construction and testing of a 750-V, 100-kW, 20-kHz bidirectional isolated dual-active-bridge dc-dc converter using four 1.2-kV 400-A SiCMOSFET/SBD dual modules. The maximum conversion efficiency from the dc-input to the dc-output terminals is accurately measured to be as high as 98.7% at 42-kW operation. The overall power loss at the rated-power (100 kW) operation, excluding the gate-drive and control circuit losses, is divided into conduction and switching losses produced by the SiC modules, iron and copper losses due to magnetic devices, and an unknown loss. The power-loss breakdown concludes that the summation of the conduction and switching losses is about 60% of the overall power loss, and that the conduction loss is nearly equal to the switching loss at the 20-kHz, 100-kW operation. © 2014 IEEE.